Development Framework on the Potential Personal Leadership in Realizing the Holistic Education - Abd Jalil, Borham (Universiti Malaysia Pahang, 2013)
This paper proposes a framework of Development Modules on the potential personal leadership in realizing the holistic education. It is related to the concept of human development where they need to be developed and nurtured in a holistic manner from both physical and spiritual aspects in accordance with the nature of creation to create a life that is pleasing to the Creator. Human today are in pursuit to get to the peak of development based on science and technology to face global challenges. Through the development of science and technology, they are fully exploiting the bounty of natural resources and facilities for the comfort of God in their lives. However, one fact that is hard to deny the nature and pattern of development carried out by leadership today have caused so much crises or problems either to the community or physical environment. Holistic education shows the development of rapid and dynamic development of national education, particularly in terms of quality, quantity, standard, excellence and credentialed recognized and accepted internationally and globally. Viewed from a broader perspective, the ability and outstanding achievements of Malaysia in developing the education sector to initiate change and dynamic development, namely human capital development, rapid economic growth, improved living standards and quality of social welfare, modernization and reform of social, cultural thought and intellectual excellence, scientific and technological development, and improve the success rate of literacy amongst the community.